Voorste rij met baard: Slotemaker de Bruïne. Oprichting Prot. Chr. Arb. Internationale? Uit archief CNV, port. 48 - Kirchbaum, Hans
Voorste rij met baard: Slotemaker de Bruïne. Oprichting Prot. Chr. Arb. Internationale? Uit archief CNV, port. 48.